Peran Pendidikan dalam Menanggulangi Kenakalan Remaja - Agnes Monica Waruwu; Hendrikus Otniel Nasozaro Harefa; Ofonai'o Gulo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to identify forms of juvenile delinquency, the role of education in addressing it, and the challenges faced at SMP Negeri 3 Gunungsitoli. The study employs a qualitative descriptive method using interviews with the school principal, guidance counselors, homeroom teachers, and students as informants. The results of the study indicate that common forms of juvenile delinquency at the school include truancy, tardiness, bringing cell phones to class, using coarse language, dating on school grounds, and violating school rules. The school plays a crucial role in addressing delinquency through counseling approaches, moral guidance, positive activities, and collaboration with parents. However, challenges include insufficient family support, limited guidance counselor staff, and low student openness. Therefore, collaboration between schools, families, and the community is essential in fostering positive character development among adolescents.